Optimizing Land Use Laws: A Comprehensive Revision of Law No. 56 of 1960 on Agricultural Land Area - Ayuni, Qurrata (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
This article discusses the expansion of Law No. 56/1960 on the Determination of Agricultural Land Area, which requires evaluation and reform. The focus is on four key regulations in the law that relate to minimum and maximum limits on agricultural land, the prohibition of agricultural land division, and agricultural pledging. This article aims to present the urgency and relevance of a strong legal political effort in formulating agricultural legislation that is more in line with current conditions and provides better protection to farmers. In order to find the urgency and relevance, this paper uses a juridical-normative methodology that emphasizes the study of literature and regulations regarding agricultural land and agrarian reform. Based on the results of the research conducted, the idea of drafting a new law using the omnibus law method is necessary to integrate various aspects of agricultural legislation into one comprehensive legal framework that guarantees the human rights and constitutional protection of citizens.